Sasquatch and the Muckleshoot - Gidwitz, Adam; Bruchac, Joseph, 1942- (Gidwitz, Adam. Unicorn Rescue Society, 2018)
"Elliot and his friend Uchenna join Professor Fauna as they travel to the Pacific Northwest and help keep a sasquatch family safe from a pack of journalists and a logging company"--